RELIGIOUS BEHAVIOR OF AGRARIAN COMMUNITY IN LINGSAR VILLAGE, LOMBOK BARAT - Suparman Jayadi; Ratih Rahmawati (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
research aimed to analyze work ethos and Sasak Islam religious behavior of agrarian community in Lingsar Village of Lombok Barat, Nusa Tenggara Barat. Sasak Islam religious behavior and work ethos of agrarian community in farming practice was the unit of analysis in this qualitative research with case study approach. Data collection was carried out through observation, in-depth interview, and documentation. To validate data, multisource evidence was used and analyzed with Weber’s social action theory. The result of research showed that religious behavior of Lingsar village’s farmer community included nerimaq (grateful), cukup (feeling enough), and ikhlas (sincere). Work ethos could be seen in social action such as working hard and diligently and farming processing land well. There was a relationship between farmer’s work ethos and Sasak Islam religious understanding of agrarian community in Lingsar Village.